The Dictator's Seduction Politics and the Popular Imagination in the Era of Trujillo - Derby, Lauren H. (Duke University Press, 2009)
The dictatorship of Rafael Trujillo, who ruled the Dominican Republic from 1930 until his assassination in 1961, was one of the longest and bloodiest in Latin American history. The Dictator's Seduction is a cultural history of the Trujillo regime as it was experienced in the capital city of Santo Domingo. Focusing on everyday forms of state domination, Lauren Derby describes how the regime infiltrated civil society by fashioning a "vernacular politics" based on popular idioms of masculinity and fantasies of race and class mobility. Derby argues that the most pernicious aspect of the dictatorship was how it appropriated quotidian practices such as gossip and gift exchange, leaving almost no place for Dominicans to hide or resist.Drawing on previously untapped documents in the Trujillo National Archives and interviews with Dominicans who recall life under the dictator, Derby emphasizes the role that public ritual played in Trujillo's exercise of power. His regime included the people in affairs of state on a massive scale as never before. Derby pays particular attention to how events and projects were received by the public as she analyzes parades and rallies, the rebuilding of Santo Domingo following a major hurricane, and the staging of a year-long celebration marking the twenty-fifth year of Trujillo's regime. She looks at representations of Trujillo, exploring how claims that he embodied the popular barrio antihero the tíguere (tiger) stoked a fantasy of upward mobility and how a rumor that he had a personal guardian angel suggested he was uniquely protected from his enemies. The Dictator's Seduction sheds new light on the cultural contrivances of autocratic power.